2023
DOI: 10.3390/gels9060453
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Fat Modifications Enabling Alternative Partially Hydrogenated Fat Products Proposed for Advanced Application

Abstract: The natural properties of oils and fats do not always allow for their direct use in industry (e.g., for food, cosmetics, and pharmaceuticals). Furthermore, such raw materials are often too expensive. Nowadays, the requirements for the quality and safety of fat products are increasing. For this reason, oils and fats are subjected to various modifications that make it possible to obtain a product with the desired characteristics and good quality that meets the needs of product buyers and technologists. The modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…To mitigate these health risks, it's crucial to avoid products containing trans fats, prioritize a diet rich in unsaturated fats, and adhere to regulations and recommendations aimed at reducing trans-fat content in foods. A. Zbikowska et al (24) showed that the biological activity of unsaturated fatty acids is disrupted during hydrogenation. This process allows obtaining products with a variety of physical and chemical characteristics and high technological value.…”
Section: Figure 1 Mechanisms Of Transisomer Formation During Hydrogen...mentioning
confidence: 99%
“…To mitigate these health risks, it's crucial to avoid products containing trans fats, prioritize a diet rich in unsaturated fats, and adhere to regulations and recommendations aimed at reducing trans-fat content in foods. A. Zbikowska et al (24) showed that the biological activity of unsaturated fatty acids is disrupted during hydrogenation. This process allows obtaining products with a variety of physical and chemical characteristics and high technological value.…”
Section: Figure 1 Mechanisms Of Transisomer Formation During Hydrogen...mentioning
confidence: 99%
“…Fats hydrogenation involves the addition of hydrogen to the double bonds present in the acidic residues of unsaturated fat in the presence of a nickel catalyst. In the food industry, hydrogen is also used in the process of synthesis of sorbitol, a sweetener [69]. In the iron and steel industry, hydrogen is considered a valuable alternative to coke, coke oven coal, and gas.…”
mentioning
confidence: 99%